Analisis Efektivitas Penagihan Pajak Bumi Dan Bangunan: Menggali Kontroversi Dan Solusi Di Kabupaten Situbondo - Moh. Rasidi; Lailatus Syarifah; Raidatus Solihah; Sofiyatun Amiliyah; Sri Rahayu (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to analyze the effectiveness of Land and Building Tax (PBB) collection in Situbondo Regency, focusing on challenges and solutions in overcoming PBB arrears. This study uses a descriptive qualitative method with data collection techniques in the form of interviews and observations at the Regional Revenue Agency (BAPENDA) of Situbondo Regency. The results of the study show that although policies such as exemption of fines and blocking of Tax Object Numbers (NOPs) have been implemented, the level of taxpayer compliance is still low due to lack of public understanding, technological limitations, and administrative constraints at the village level. Therefore, a more innovative approach is needed, such as the development of a data-based billing system and increasing socialization and education to the public. The implication of this study is the importance of policy integration and technical capacity building in UN management to achieve optimal revenue targets and support regional development.